1988
DOI: 10.1111/j.1532-5415.1988.tb01806.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Cornell Scale in Nondemented Patients

Abstract: The Cornell scale is a 19-item clinician-administered scale of depression that uses information from interviews with both patients and their caregivers. The Cornell scale has been validated in demented patients. In this study, the Cornell scale was psychometically tested in nondemented geriatric subjects by administering it to 15 depressed patients, 15 patients with other psychiatric diagnoses, and 15 normal control subjects. The Cornell scale had high interrater reliability (Cohen's kappa = 0.74), internal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
122
0
4

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(128 citation statements)
references
References 25 publications
2
122
0
4
Order By: Relevance
“…Performance in the MMSE, adjusted to the educational level, had to be greater than or equal to 21 for one to three years of schooling, greater than or equal to 24 for four to seven years and greater than or equal to 26 for individuals with eight or more years of schooling 9 . Score on the CSD had to be less than or equal to seven points and on GDS, lower than five in order to rule out depression 11,12 . The FAB consists of six subtests: similarities, lexical fluency (letter s), motor series, conflicting instructions, go / nogo, and prehension behavior.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Performance in the MMSE, adjusted to the educational level, had to be greater than or equal to 21 for one to three years of schooling, greater than or equal to 24 for four to seven years and greater than or equal to 26 for individuals with eight or more years of schooling 9 . Score on the CSD had to be less than or equal to seven points and on GDS, lower than five in order to rule out depression 11,12 . The FAB consists of six subtests: similarities, lexical fluency (letter s), motor series, conflicting instructions, go / nogo, and prehension behavior.…”
Section: Methodsmentioning
confidence: 99%
“…All participants were submitted to the MMSE, the Brazilian version of the FAB and the Cornell Scale of Depression (CSD) or the Geriatric Depression Scale (GDS) [9][10][11][12] . Performance in the MMSE, adjusted to the educational level, had to be greater than or equal to 21 for one to three years of schooling, greater than or equal to 24 for four to seven years and greater than or equal to 26 for individuals with eight or more years of schooling 9 .…”
Section: Methodsmentioning
confidence: 99%
“…In research studies, internal consistency, interrater reliability, and concurrent validity were shown to be acceptable, 31,78,162 and the CSDD was shown to have acceptable psychometric properties in severe dementia. 78 Sensitivity to change was demonstrated in a few trials.…”
Section: Depression In Non-pd Patientsmentioning
confidence: 99%
“…[163][164][165][166] Informed other ratings on the CSDD in patients with dementia were shown to have higher sensitivity for correctly diagnosing depression than other depression scales, including the BDI, the Ham-D, and the GDS (all modified for caregiver rating). 97 Although there is limited data on the reliability, validity, and sensitivity of the CSDD in nondemented elderly patients, 162,167 it has also been recommended as a useful scale for screening older adults for a diagnosis of depression. 168 The scale is in the public domain (see, for example, Table 3 located in Supplementary Material) and has been translated into several European and Asian languages.…”
Section: Depression In Non-pd Patientsmentioning
confidence: 99%
“…• Escala Cornell para depressão em demência (59) (ANEXO J): Trata-se de um instrumento de rastreio de depressão validado tanto para idosos com diagnóstico de demência quanto para idosos saudáveis do ponto de vista cognitivo (60) . Constituído por 19 itens descritores de sinais relacionados ao humor, a distúrbios do comportamento, a sinais físicos, às funções cíclicas e a distúrbio ideativo.…”
Section: Instrumentos De Avaliação Cognitivaunclassified